2020
DOI: 10.3329/ajmbr.v6i3.49793
|View full text |Cite
|
Sign up to set email alerts
|

Spawning and developmental biology of endangered Pabdah catfish, Ompok pabda (Hamilton, 1822)

Abstract: Pabdah catfish, Ompokpabdawas collected from the Old Brahmaputra river and successfully induced to breed by injecting pituitary gland extract to evaluate spawning performances and developmental stages under a photo microscope from February 2018 to August 2018. In this study, absolute fecundity of the O. pabdafemales varied from 6,676 to 20,410 eggs per fish. The GSI value of male and female was lower during September and gradually attained its maximum level in June with the highest average value 6.75±0.2 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Chakrabarty et al (2008) and Hossen et al (2014c) observed first cleavage in about 30 min after fertilization followed by 16 celled stages in 70 min. Tumpa et al (2020) have found gastrula stage in O. pabda within 4.50 to 5.00 h. According to Dey et al (2015) gastrula period were observed to be from 3.05 to 6.33 h in Botia lohachata fish. In a prior study, Puvaneswari et al (2009) also reported that H. fossilis took 7 h to reach in gastrula stage.…”
Section: Observation Of the Early Embryonic Development Of M Cavasiusmentioning
confidence: 90%
“…Chakrabarty et al (2008) and Hossen et al (2014c) observed first cleavage in about 30 min after fertilization followed by 16 celled stages in 70 min. Tumpa et al (2020) have found gastrula stage in O. pabda within 4.50 to 5.00 h. According to Dey et al (2015) gastrula period were observed to be from 3.05 to 6.33 h in Botia lohachata fish. In a prior study, Puvaneswari et al (2009) also reported that H. fossilis took 7 h to reach in gastrula stage.…”
Section: Observation Of the Early Embryonic Development Of M Cavasiusmentioning
confidence: 90%
“…To estimate the hatching rate, fertilized eggs were scooped out after 24 h of spawning and the number of hatchlings released from the eggs was counted. The data obtained from the samples were analysed for GSI, fecundity, fertilization and hatching rate using the following formulae (Ferosekhan et al, 2019(Ferosekhan et al, , 2021Tumpa et al, 2020)…”
Section: Reproductive Parametersmentioning
confidence: 99%
“…The ovaries of O. bimaculatus carry unripe eggs from January to April (Malla & Banik, 2015). Hatching was not observed TA B L E 3 Influence of different photoperiod regimes on spawning response (%), fertilization rate (%), and hatching rate (%) of O. bimaculatus broodfish (n = 3) reared for 45 days June to August (Ali et al, 2016;Tumpa et al, 2020). Compared with previous reports (Basavaraja et al, 2013;Hussan et al, 2020) on the hatching rate (50%-78%) of O. bimaculatus during the breeding season, the 12L:12D group had a higher hatching rate (85%) in April.…”
Section: Absolute Fecunditymentioning
confidence: 99%
“…In Sundarbans, climate change is a virtual event as many fish species in this area are declining due to climate change, exploitation, habitat alteration, as well as pollution . Physical and biogeochemical aspects of aquatic ecosystems, such as pH, temperature, and oxygen concentration, can be affected by climate change (Tumpa et al, 2020), wind patterns and flow, and upwelling activity. These changes immediately impact aquatic nutrient enrichment and the ecophysiology and ecology of underwater creatures (Dasgupta et al, 2017;Rahaman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%